Characterization of the Human Mitochondrial Translational Release Factor(s) - HR Soleimanpour; ZM Chrzanowska-Lightowlers; RN Lightowlers (Tehran University of Medical Sciences, 2005)
Mitochondria, the powerhouses of the cell, possess their own translational system seemingly inherited from their proteo-bacterial ancestor. Termination of translation in bacteria is mediated by Release Factors 1, 2 and 3 (RF1, 2 & 3), the first two of which recognise stop codons UAA, UAG and UGA, while RF3 just enhances the efficiency of termination. In human mitochondria where translation termination is triggered by four stop codons (UAA, UAG, AGG and AGA), only one candidate gene (MTRF1) is purported in silico to encode a functional mitochondrial release factor. Having searched the human genome database, we have found another candidate (NP_061914) potentially capable of acting as mitochondrial release factor based upon its high similarity to bacterial RF1 and MTRF1. To determine whether these two candidates are located in the mitochondrion, they have been cloned into a GFP expression vector (pGFP3) and transfected into HeLa cells for 48 hours followed by staining with Mitotracker Red CMXRos. Analysis of the cells with Fluorescence Microscopy equipped with Metamorphosis software showed localization of the two GFP chimaeras to mitochondria, implying mitochondrial localization of MTRF1 and "NP_061914". To determine whether "NP_061914" is actually imported into mitochondria, a radiolabelled product was generated in vitro and incubated with isolated rat liver mitochondria. N-terminal cleavage was demonstrated and the matured protein became insensitive to added proteinase, consistent with "NP_061914" accessing the mitochondrial matrix. This protein has now been renamed "MTRF2".